INFORMATION SYSTEMS EMPOWERED BY BIG DATA – A REVIEW OF APPLICATIONS IN SMES’ RESILIENCE AND PERFORMANCE - Ramdana, Adi Dadan; Sumiarsih, Mia; Sakinah, Awit Marwati; Yulianti, Lisna; Mutholib, Azis (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
Big Data Analytics (BDA) is increasingly helping Small and Medium-sized Enterprises (SMEs) improve resilience, efficiency, and decision-making. This Systematic Literature Review (SLR) explores the adoption of BDA in SMEs, highlighting its benefits, challenges, and key trends. Using the PRISMA framework, a structured search in Scopus identified 60 studies, with 42 meeting the inclusion criteria (2015–2025). The findings show that BDA supports SMEs in crisis management, supply chain optimization, and customer analytics, contributing to long-term business sustainability. However, several barriers limit its adoption, including high costs, technical complexity, and data security concerns. To understand its impact, this study applies Resource-Based View (RBV), Technology-Organization-Environment (TOE), and Dynamic Capabilities View (DCV) frameworks. To address adoption challenges, government support through financial incentives, improved digital infrastructure, and specialized training programs is recommended. SMEs should focus on cloud-based analytics, strategic collaborations, and building a data-driven culture to maximize BDA benefits. Although BDA has great potential, its adoption among SMEs remains uneven. Future research should explore its combination with Artificial Intelligence (AI) and Machine Learning (ML) to enhance competitiveness and drive innovation in a fast-changing business environment